Giant clams in Asia and the pacific (Australian Centre for International Agricultural Research, 1988)
Giant clams have been over exploited throughout much of their geographic range, and in certain areas some species are now extinct. An ACIAR-sponsored project has increased the knowledge of the life cycle of giant clams, developed methods for culture, and explored the potential for restocking tropical reefs with giant clams and for farming them. This publication brings together the literature and results of most of the world's research on giant clams.